2011
DOI: 10.3923/pjbs.2011.658.663
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Biguanide Vs. Statin in Polycystic Ovary Syndrome: A Randomized Clinical Trial

Abstract: Various classes of medication are currently being used in Polycystic Ovary Syndrome (PCOS) patients including the biguanides and the statins. However, their efficacies are rarely compared. This study aimed to compare efficacy ofa biguanide and a statin in treating PCOS. In a randomized double-blind clinical trial, 400 women with PCOS were recruited within 15 months in Taleghani Hospital. They randomly received either a biguanide (metformin 500 mg three times daily) or a statin (simvastatin 20 mg daily) for thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 6 publications
1
20
0
1
Order By: Relevance
“…18,22,23,24 Both Navali et al's and Fruzzetti et al's studies demonstrated that statins (20mg/day simvastatin and 4 g/day myo-inositol, respectively) are superior to 1.5g/ day metformin for treating acne (P<0.05) among other PCOS parameters. 15,25 Combination therapy of metformin 850mg with pioglitazone 7.5mg daily, flutamide 62.5mg daily for 6 months, or oral metformin 850mg twice a day and simvastatin 20mg daily also demonstrated clinical efficacy for improvement in acne…”
Section: Acnementioning
confidence: 99%
See 2 more Smart Citations
“…18,22,23,24 Both Navali et al's and Fruzzetti et al's studies demonstrated that statins (20mg/day simvastatin and 4 g/day myo-inositol, respectively) are superior to 1.5g/ day metformin for treating acne (P<0.05) among other PCOS parameters. 15,25 Combination therapy of metformin 850mg with pioglitazone 7.5mg daily, flutamide 62.5mg daily for 6 months, or oral metformin 850mg twice a day and simvastatin 20mg daily also demonstrated clinical efficacy for improvement in acne…”
Section: Acnementioning
confidence: 99%
“…Women with a history of PCOS with acne, and one study involving men with refractory acne, (total n=1,587 patients) were treated with oral metformin (dose range, 1,000-2,550mg/day). All except three studies [13][14][15] reported significant improvement in acne in female patients with PCOS. Only Fabbrocini et al's study assessed the effects of metformin and a low glycemic diet on male subjects with resistant acne.…”
Section: Acnementioning
confidence: 99%
See 1 more Smart Citation
“…Two (3.4%) RCTs compared saxagliptin with metformin 33,74 . Two (3.4%) RCTs compared simvastatin with metformin 55,60 . Two (3.4%) RCTs assessed metformin with NAC 41,61 .…”
Section: Resultsmentioning
confidence: 99%
“…7 Penelitian terhadap pasien yang menjalani operasi seksio sesarea dengan teknik regional anestesia yang mendapatkan infiltrasi 20 mL lidokain 1% dengan 1:100.000 adrenalin menunjukkan bahwa tempat infiltrasi pada luka operasi, yaitu subkutis, intramuskular, dan subkutis ditambah intramuskular secara signifikan dan efektif dapat mengurangi nyeri dan kebutuhan analgetik rescue bila dibanding dengan plasebo. 8 Hasil penelitian lain menunjukkan bahwa infiltrasi selektif terhadap otot rektus pada luka operasi tanpa jaringan fasia dan subkutis di sekitarnya dengan 0,5% bupivakain signifikan mengurangi nilai nyeri serta kebutuhan morfin per jam selama 2 jam pascaoperasi dan total kebutuhan morfin 6 jam pascaoperasi pada histerektomi per abdominal.…”
Section: Pendahuluanunclassified